A cross sectional study of p504s, CD133, and Twist expression in the esophageal metaplasia dysplasia adenocarcinoma sequence. Issue 3 (25th February 2014) - Ahmad, J.; Arthur, K.; Maxwell, P.; Kennedy, A.; Johnston, B. T.; Murray, L.; McManus, D. T.
Summary The incidence of esophageal adenocarcinoma has increased dramatically over recent years and Barrett's esophagus is considered the most established risk factor for its development. Endoscopic surveillance of Barrett's esophagus is therefore recommended but hinges on histological interpretation of randomly taken biopsies which is poorly reproducible. The use of biomarkers presents an opportunity to improve our ability to risk‐stratify these patients.We examined three biomarkers namely p504s, CD133, and Twist in the setting of Barrett's esophagus, low‐grade dysplasia, and esophageal adenocarcinoma to evaluate differential expression between benign, dysplastic, and malignant Barrett's tissue in an exploratory cross‐sectional study. Twenty‐five cases each of Barrett's esophagus, low‐grade dysplasia, and esophageal adenocarcinoma were included along‐with 25 cases of esophagectomy resections for Barrett's adenocarcinoma. The biomarkers were immunostained on automated Ventana® immunostainer. The biopsies were assessed for biomarker expression by two independent observers. Granular cytoplasmic staining of p504s was observed in dysplastic Barrett's biopsies and esophageal adenocarcinoma but not in Barrett's esophagus. Apical and membranous CD133 expression was also observed in dysplastic Barrett's and esophageal adenocarcinoma. Nuclear Twist expression was seen predominantly in stromal cells. There was increased p504s expression in dysplastic Barrett's esophagus and esophageal adenocarcinoma compared with controls. CD133 expression was detected for the first time in esophageal adenocarcinoma and dysplastic Barrett's esophagus. Twist expression was not convincing enough to be labeled as Barrett's biomarker. p504s and CD133 have the potential to differentiate benign from malignant Barrett's tissue in this exploratory study. Their validity should be established in prospective longitudinal studies.